Somatic Multiplication in Eucalyptus camaldulensis Through Leafy Cuttings - Vakshasya, Rajnish K.; Rawat, M. S. (Indian Forester, 1984)
Viewing the increasing demand of eucalypts planting under various recently developed programmes. This article presents the importance of somatic multiplication through rooting of cuttings in Eucalyptus camaldulensis, enabling the scientists to conserve & multiply the plus phenotypes and varieties developed and the consumer to barvest the best in shortest possible span of time.